2015
DOI: 10.1039/c5cp04009d
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the role of Pb2+ in the stability of organic–inorganic hybrid perovskite CH3NH3Pb1−xCdxI3: an experimental and theoretical study

Abstract: This paper presents the synthesis of organic-inorganic hybrid perovskite CH3NH3Pb1-xCdxI3. The effect of incorporating Cd(2+) or Pb(2+) on the stability of the perovskite structure was analysed from a theoretical and experimental viewpoint. The XRD results showed that the tetragonal perovskite structure was formed for x values of up to 0.5, which seems to indicate that the presence of a considerable amount of Pb(2+) is necessary to stabilise the structure. In turn, UV-Vis spectroscopy showed how the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
(111 reference statements)
3
19
1
Order By: Relevance
“…Journal of Nanomaterials [6,38]. Thus, the contribution of Cd s-states is also included in Figure 7 and it is shown that the contribution of the s-states of the Cd to the origin of the CB plays a fundamental role in the decrease in the band gap, as reported elsewhere [38].…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Journal of Nanomaterials [6,38]. Thus, the contribution of Cd s-states is also included in Figure 7 and it is shown that the contribution of the s-states of the Cd to the origin of the CB plays a fundamental role in the decrease in the band gap, as reported elsewhere [38].…”
mentioning
confidence: 56%
“…The values are 1.5, 2.2, and 1.19Å for NH 4 + , I − , and Pb 2+ , respectively. In turn, the effective ionic radius of [CH 3 NH 3 ] + was calculated according to a rigid sphere model with free rotation of its centre of mass, as reported in the literature [38]. The value obtained is 1.74Å.…”
Section: X-raymentioning
confidence: 99%
See 1 more Smart Citation
“…DFT‐periodic calculations were performed by using the Vienna ab initio simulation package (VASP) with the projector‐augmented wave (PAW) method . The number of plane waves in VASP was controlled by a cutoff energy, set in our calculations to E cut =500 eV, to satisfactorily describe the system . The electron exchange and correlation were treated within the generalised gradient approximation (GGA) .…”
Section: Methodsmentioning
confidence: 99%
“…the devices are exposed to moisture, continuous illumination, thermal-stress and oxygen [40,[107][108][109][110][111][112][113]. The basic degradation mechanism in PSCs is the breakdown of perovskite material under moisture or heat stress, which results in the segregation of MAPbI3 into its constituents PbI2 and MAI [114][115][116]. It is summarized as: CH3NH3PbI3 → PbI2 + CH3NH2↑ +HI↑ The perovskite CH3NH3PbI3 thin films are found to undergo decomposition under thermal stress at a temperature between ~100 °C [117] and 140 °C [118]; the decomposition rate increases further as the temperature is increased [119].…”
Section: Stabilitymentioning
confidence: 99%